1951
DOI: 10.1172/jci102453
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cation Exchanges in Metabolic Alkalosis 1

Abstract: It is now well known that disturbances in the electrolyte patterns of the intracellular fluid, as well as in those of the extracellular fluid, may play a significant role in many disease states. Darrow and associates (1) (2)(3)(4)(5)(6)(7)(8), by study of the distribution of radioactive sodium (9), and by tissue analyses of skeletal muscle (10) and of erythrocytes (9, 11). These observations have suggested that both low potassium intake and hyperadrenocortical function are implicated in the etiology of this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1951
1951
1965
1965

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…by a large but transient retention of sodium, an observation similar to that made by Elkinton, Squires, and Crosley (30). Sodium retention may have been related to the reversible disturbances in renal function observed in the present patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…by a large but transient retention of sodium, an observation similar to that made by Elkinton, Squires, and Crosley (30). Sodium retention may have been related to the reversible disturbances in renal function observed in the present patients.…”
Section: Discussionsupporting
confidence: 88%
“…Sodium retention (30,40,41), elevated blood nitrogen concentration (40), and reduced urea clearance (41) may be in part due to the reduction in glomerular filtration. Renal tubular damage could explain the isosthenuria in these and other cases of potassium depletion (38,39,42) as well as the polyuria in potassium-deficient dogs (43) and rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…A body deficiency of potassium is known to exist in diabetic acidosis and coma (4), in certain gastrointestinal disorders (5), and in certain postoperative conditions (6). With severe renal damage, retention of potassium may occur.…”
Section: Commentmentioning
confidence: 99%
“…Palmer and Van Slyke (2) and later Hartmann and Senn (3) found that the rise in serum bicarbonate was such that the dose of alkali was apparently distributed through a volume equal to two-thirds of the body weight, a fraction which they believed represented the total body water. Since both bicarbonate ions (4,5) and the major portion of sodium ions are not freely diffusible across the cell membrane, some explanation must be sought for the discrepancy between the value stated above and the now commonly accepted 1 Laboratory facilities were aided by grants from the National Heart Institute, U.S.P.H.S., the C. Mahlon Kline Fund of the Department of Medicine, and the Committee on the Advancement of Research of the University of Pennsylvania. The help of the laboratory staffs and of the clinical staff of the Hospital is gratefully acknowledged.…”
mentioning
confidence: 91%
“…Disturbances in the exchanges of certain intracellular electrolytes which occur in patients with metabolic alkalosis, have been described in the previous paper (1). Clues to the direction and magnitude of these disturbances were obtained by calculating from balance measurements the alterations in body fluids produced by replacement therapy.…”
mentioning
confidence: 99%